Pelatihan Membanyakan Herbisida Sendiri Untuk Pengurangan Biaya Produksi Petani - Warlinson Girsang; Rosmaria Girsang; Olivia J Nainggolan; Deana Manihuruk; Amsal Randy Turnip; Jondarta Girsang; Basriadi Saragih (Universitas, 2022)
Herbicides are needed by farmers to control weeds in their farming land. Although the price of herbicides is expensive, farmers always try to buy them. The need for working capital to buy herbicides is one of the factors that drives the increase in farm production costs. The initial survey of potential partner farmers illustrates that farmers are familiar with and have used various types of herbicides. However, all farmers in Dusun Bah Bulawan do not know how to make or reproduce herbicides. All farmers depend on buying commercial herbicides from agricultural kiosks, which are relatively expensive and tend to increase from year to year. Based on the situation analysis of partner farmers, a concept was formulated, namely how to make farmers' knowledge change from not knowing to knowing in terms of multiplying herbicides. The strategy of the activities carried out is to organize training. Farmers are equipped with technological knowledge to reproduce their own herbicides. With the skills of being able to reproduce their own herbicides, it is hoped that farmers can save production costs. Because the cost of buying herbicides can be reduced by a significant amount. The general objective of training activities is to help farmers overcome their problems and reduce farm production costs. Meanwhile, the specific objective is to increase the welfare of farmers through savings in farm production costs. Benefits of the activity: the knowledge and skills of farmers will increase, especially the technology for increasing herbicides. While the impact of activities: (a). Farmers gain additional knowledge of technology transfer from universities and create synergistic cooperation between universities and the community. (b). Farmers know more about the use of herbicides as weed control. (c). Farmers' knowledge changed from not knowing to knowledgeable in terms of multiplying herbicides. (d). Farmers are able to multiply their own herbicides to reduce farm production costs. (e). The level of income and welfare of farmers is expected to increase, because production costs for controlling weeds can be saved